Whether CCS technologies will exacerbate the water crisis in China? —A full life-cycle analysis. (December 2020) - Yang, Lin; Lv, Haodong; Jiang, Dalin; Fan, Jingli; Zhang, Xian; He, Weijun; Zhou, Jinsheng; Wu, Wenjing
Abstract: Carbon capture and storage (CCS) is an indispensable technology for achieving emission reduction targets, but it is a resource-intensive process requiring a large amount of water. Based on the full life-cycle analysis, this paper firstly reviews the existing research regarding not only the water withdrawal and consumption for pulverized coal (PC), nature gas combined cycle (NGCC), and integrated gasification combined cycle (IGCC) power plants, but also the water production resulting from CO2 -enhanced water recovery (CO2 -EWR). And then a case study is conducted using the practical data of 35 PC power plants satisfying source-sink matching principle. We found that: (1) CCS can reduce 140 Mt/a CO2 emissions with a capture rate of 90%, whereas water withdrawal will increase by 174.9%, and water consumption will increase by 150.5% (without EWR) and 36.9% (with EWR). Obviously, the CO2 -EWR can drastically reduce water consumption. (2) Capture process contributes most to the water usage. Particularly, PC with circulating cooling requires plenty of water while the increase rate only doubles with CCS. By contrast, although water withdrawal for PC with air cooling is relatively small, the increase rate expands 9 times due to cooling the high-temperature flue gas during capture process. (3) The annual water withdrawal in Ordos Basin and Bohai Bay Basin increases by 347% and 131%, respectively, while water consumption increases only by 30.1% and 45.6%, respectively. Overall, enhancing the condensate recovery treatment during the capture process and the CO2 -EWR during the storage process can be considered to deal with water scarcity challenge. Highlights: CCS is a resource-intensive technology requiring a large amount of water. Carbon capture process contributes most to the total water usage. Water for air cooling grow greatly while that for circulating cooling doubles. CO2 -EWR can effectively reduce the water consumption to some extent. CCS will exacerbate the water resources crisis in some areas of China.